Selective β-N-acetylhexosaminidase from Aspergillus versicolor-a tool for producing bioactive carbohydrates - Bojarová, Pavla; Kulik, Natallia; Slámová, Kristýna; Hubálek, Martin; Kotik, Michael; Cvačka, Josef; Pelantová, Helena; Křen, Vladimír (Applied microbiology and biotechnology, 2019)
β-N-Acetylhexosaminidases (EC 3.2.1.52) are typical of their dual activity encompassing both N-acetylglucosamine and N-acetylgalactosamine substrates. Here we present the isolation and characterization of a selective β-N-acetylhexosaminidase from the fungal strain of Aspergillus versicolor. The enzyme was recombinantly expressed in Pichia pastoris KM71H in a high yield and purified in a single step using anion-exchange chromatography. Homologous molecular modeling of this enzyme identified crucial differences in the enzyme active site that may be responsible for its high selectivity for N-acetylglucosamine substrates compared to fungal β-N-acetylhexosaminidases from other sources. The enzyme was used in a sequential reaction together with a mutant β-N-acetylhexosaminidase from Talaromyces flavus with an enhanced synthetic capability, affording a bioactive disaccharide bearing an azido functional group. The azido function enabled an elegant multivalent presentation of this disaccharide on an aromatic carrier. The resulting model glycoconjugate is applicable as a selective ligand of galectin-3 - a biomedically attractive human lectin. These results highlight the importance of a general availability of robust and well-defined carbohydrate-active enzymes with tailored catalytic properties for biotechnological and biomedical applications.
Keywords: Models, Molecular; chromatografie iontoměničová; katalytická doména; Catalytic Domain; Disaccharides; Protein Conformation; beta-N-acetylhexosaminidasy; konformace proteinů; molekulární modely; Talaromyces; rekombinantní proteiny; Pichia; Aspergillus; Gene Expression; disacharidy; Recombinant Proteins; beta-N-Acetylhexosaminidases; exprese genu; Chromatography, Ion Exchange